ANALISIS INDEKS KEPUASAN PENGGUNA LAYANAN PUSAT ARSIP INAKTIF (RECORD CENTER) ARSIP NASIONAL REPUBLIK INDONESIA - Martino Martino (Jurnal Natapraja: Kajian Ilmu Administrasi Negara, 2018)
ANRI Records Center has a strategic role for the record management. ANRI as a national archive institution has the consequence that ANRI records center is considered a role model by the public in terms of institutional aspects of the records center, facilities and infrastructure, management and service management. This consequence requires ANRI Record Center to have good governance in the implementation of its duties and functions. This study aims to analyze costumer satisfaction index of ANRI Records Center services using Importance-Performance Analysis (I-P Analysis) through combination of gap analysis and quadrant analysis. The research used quantitative method with descriptive data analysis on costumer satisfaction index and I-P Analysis. The result of research shows index of satisfaction ANRI Records Center that is 3,23 with value of conversion index equal to 80,47. It shows the quality of service classified as "B" and the performance of service units predicated "Good". However, the Gap Analysis shows a negative gap value which means that the performance of each service indicator is not as optimal as the user expectation. The service elements that should be a performance improvement priority include: service convenience; completeness of service and service procedures.